DAMPAK PERKEMBANGAN BAHASA ANAK USIA 4-6 TAHUN OLEH IBU BEKERJA YANG MEMBACA NYARING - Putri Zalika Laila Mardiah Kesuma; Putri Rizki Amalia Badri; Wahyu Akbar Irsandy; Rury Tiara Oktariza; Ratika Febriani (Collaborative Medical Journal, 2023)
Reading aloud or read aloud is a method of reading texts aloud using reading media in the form of illustrated textbooks accompanied by expressions, intonation and interaction between the reader and listener. Reading aloud can be done by parents, especially mothers, both housewives and also working mother. It can impact a child's focus and attention span and stimulates discussion and interaction. This study aims to determine the relationship between the habit of reading aloud by working mothers and the language development of their children aged 4-6 years in Kindergartens Xaverius 3, 4 and 9, Palembang. The type of research used is analytical observational with a cross sectional design. The population of this study were working mothers with children aged 4-6 years who attended kindergartens Xaverius 3, 4 and 9, Palembang. The sample used was 40 respondents who met the inclusion and exclusion criteria. Data collection was carried out using a read aloud questionnaire and a pre-development screening questionnaire (KPSP). The results of the univariate analysis provide an overview of the frequency distribution regarding the mother's last education, the mother's occupation, the habit of reading books using the read aloud method, and the language development of children aged 4-6 years. Meanwhile, bivariate analysis carried out using the chi-square test obtained a p-value of 0.025 (P<0.05) so we can conclude that there is a significant relationship between the habit of reading aloud and the language development of children aged 4-6 years.